Peran Literasi Digital dalam Meningkatkan Daya Saing UMKM di Era Ekonomi Digital - Yasnimar Ilyas; Mujito Mujito; Eidelweijs Andririnjani Putri (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the role of digital literacy in enhancing the competitiveness of MSMEs in the era of the digital economy. The research method employed was a survey by distributing questionnaires to 35 UMKM actors in the Jabodetabek area. The findings reveal that the level of digital literacy among UMKM is categorized as good, particularly in aspects of technology access, technical skills, digital communication, and the use of online transaction services. Digital literacy has a positive impact on business performance, including increased revenue, market expansion, operational efficiency, and product competitiveness. However, challenges remain, such as high digital promotion costs, limited knowledge in content management, and uneven internet infrastructure. This study highlights that improving digital literacy is a key factor for UMKM to survive and remain competitive amid the rapid development of the digital economy.